Severe chronic spontaneous urticaria in children – treatment options according to the guidelines and beyond – a 10 years review. (17th February 2022) - Staubach, Petra; Peveling-Oberhag, Adriane; Lang, Berenice M.; Zimmer, Sebastian; Sohn, Anna; Mann, Caroline
Abstract: This is a retrospective study of 18 children with chronic spontaneous urticaria (CSU), where standard therapies, including up-dosing of antihistamines and omalizumab, were unable to cure the disease and where alternative strategies with experimental and off-label medication had to be used. Materials: Being aware that our questionnaire is validated only for elder children or adults, we utilized the UAS7 to monitor disease control with the help of the parents. Results: The UAS7 score decreased from a mean of 25 to an average of 13 after 8 weeks of therapy in 13 patients. Five patients had no significant reduction of UAS7 by week 8. In two of five patients, where periodic improvement was seen, omalizumab therapy was continued and showed complete response after 1–2 years. In three children, alternative treatments with cyclosporine and dupilumab, approved by the ethics committee, showed symptom improvement from a mean UAS7 of 29 to a mean value of 6. Conclusions: When omalizumab therapy including up-dosing strategies or shortened interval shows no symptom improvement, alternative therapies, sometimes off-label have to be considered in time.